Game Multimedia in Numeracy Learning for Elementary School Students. (March 2017) - Rohendi, D; Sumarna, N; Sutarno, H
Abstract: Numeracy is one of the basic skills for elementary students to understand further concepts of mathematics. However teaching numeracy is still using recitation that can overload student's memory and make them reluctant to learn mathematics, so an innovative way by using multimedia to attract student interest in numeracy is needed. Therefore, the purpose of this study are: 1) to develop numeracy learning multimedia for elementary school students; and 2) to find out whether the implementation of numeracy learning multimedia can improve the students numeracy skills, and how is the response of elementary school students by using multimedia in learning numeracy? The results showed that multimedia can improve students' numeracy skill which is quit medium and the student response by using multimedia in numeracy learning are good.